Profiling winding up companies and reason for not rescuing their business / Norziana Lokman …[et al.] - Lokman, Norziana; Mohammed, Nor Farizal; Mohamed, Nor Azida; Mohamad Khudzari, Julizaerma (Universiti Teknologi MARA, 2021)
The old regime of corporate rescue seems to be suitable for larger companies which left small companies with no option other than seeking winding up, which involves liquidation and dissolution process. Corporate Rescue Mechanism is a new rescue mechanism introduced by the Companies Commission of Malaysia (CCM) in March 2018 to help small and medium enterprises (SMEs) under financial distress rescue their businesses and avoid liquidation. This study investigates and profiles why a company resorts to winding up. This study used a purposive sampling technique to select the sample of companies to be involved in the study. This study used secondary data which is accessible from the 2017 to 2019 winding up statistics/reports of the Malaysia Department of Insolvency. This study employed a descriptive statistic to analyse the data. Results reveal that the key reason behind the choice made by the financially distressed company is the inability to pay debts. In addition, an inherent risk related to the specific nature of business sectors, such as trade, wholesale and retail, construction and financial, insurance, property and investment services is expected to have a high tendency to opt for winding up instead of rescuing or rehabilitating their business. Furthermore, small (in terms of capital amount) and young companies (age or year of operation) tend to be vulnerable to winding up. The findings of the study can assist business owners and business rescue practitioners guide distressed companies in making better decisions (rescue or dissolve) and to plan and manage their business operations efficiently. The policy maker may consider helping small companies by providing funding with lower or zero interest and longer payback periods. It is hoped that the new Malaysian corporate rescue mechanism can help enhance the ability of the company to survive and sustain for a longer period.